PLASMA CONCENTRATIONS AND CORRELATIONS OF NATRIURETIC PEPTIDES AND OXYTOCIN DURING LABOR AND EARLY POSTPARTUM PERIOD - (:unkn) unknown (EDITURA ACAD ROMANE, 2017)
Context. Natriuretic peptides (NP) and oxytocin (OT) play an important role in cardiovascular and hydro electrolytic homeostasis. Changes in NP levels and their roles in cardiovascular adaptations in pregnancy and labor have not been clear. Objective. The present study aimed to investigate the changes and correlations in plasma levels of atrial natriuretic peptide (ANP), C-type natriuretic peptide (CNP), B -type natriuretic peptide (BNP) and OT during labor and the postpartum period. Study design. Blood samples were collected from 29 healthy pregnant women in the active phase of spontaneous labor, 15 minutes after delivery and 3 hours postpartum. Plasma levels of OT and the stable N-terminal fragments of NPs (NT-proANP, NT-proCNP, NT-proBNP) were measured using enzyme or electrochemiluminescence immunoassays. Results. The plasma levels of NT-proANP and NT-proCNP significantly decrease 3 hours postpartum compared to the active phase of labor and to 15 minutes after delivery. The plasma NT-proBNP levels significantly higher after delivery and 3 hours postpartum compared to the active phase of labor. A significant correlation exists between OT and NT-proANP levels during the active phase of labor and 15 minutes after delivery. Conclusions. The data show that during labor and postpartum, the plasma concentrations of the NPs change differently. Elevations in NT-proBNP after delivery suggest that BNP may be involved in postpartum adaptations. The correlations between OT and ANP levels indicate that OT may be partly responsible for the increased levels of ANP and may have a role in the modification of the cardiovascular system.
Keywords: Natriuretic peptides; Oxytocin; Pregnancy; Labor; Postpartum; NORMAL HUMAN-PREGNANCY; HEMODYNAMIC-CHANGES; CARDIOVASCULAR REGULATION; PREECLAMPTIC PREGNANCIES; EARLY PUERPERIUM; RAT; HEART; EXPRESSION; RECEPTORS; SYSTEM